2009
DOI: 10.1038/cmi.2009.43
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signaling Pathway, Inflammation and Colorectal Cancer

Abstract: There is growing evidence for a connection between inflammation and tumor development, and the nuclear factor kappa B (NF-B), a proinflammatory transcription factor, is hypothesized to promote tumorigenesis. Although the genetic evidence for the hypothesis has been lacking, recent papers have lent credence to this hypothesis. It has been reported that constitutive NF-B activation in inflammatory bowel diseases (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
289
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(306 citation statements)
references
References 94 publications
8
289
0
9
Order By: Relevance
“…27,28 Numerous proangiogenic and proinflammatory genes, such as VEGF, IL-8 and COX-2, are transcriptionally regulated by the NF-kB pathway. 16 We found that GW9508 treatment elicited phosphorylated-IkBa at Ser32 in CRC cells, which is essential for the release of active NF-kB. However, blocking the activation of IkBa completely abrogated GPR120 signaling-induced production of VEGF, IL-8 and COX-2, and angiogenesis.…”
Section: Gpr120 Is Induced In Human Crc Tissues and Its Expression Ismentioning
confidence: 71%
See 1 more Smart Citation
“…27,28 Numerous proangiogenic and proinflammatory genes, such as VEGF, IL-8 and COX-2, are transcriptionally regulated by the NF-kB pathway. 16 We found that GW9508 treatment elicited phosphorylated-IkBa at Ser32 in CRC cells, which is essential for the release of active NF-kB. However, blocking the activation of IkBa completely abrogated GPR120 signaling-induced production of VEGF, IL-8 and COX-2, and angiogenesis.…”
Section: Gpr120 Is Induced In Human Crc Tissues and Its Expression Ismentioning
confidence: 71%
“…GRP120 signaling induces angiogenesis in CRC cells through activation of the PI3K/Akt-NF-kB pathway GPR120 triggers various cellular pathways to exert disparate functions. 7,8 As the above-identified induced proangiogenic genes are known downstream targets of NF-kB, 16 we focused on the role of the NF-kB pathway in the production of proangiogenic mediators. First, we performed western blotting analysis to determine whether the NF-kB pathway was modulated by GPR120 signaling.…”
Section: Gpr120 Is Induced In Human Crc Tissues and Its Expression Ismentioning
confidence: 99%
“…Smad 2, 3 and 4) can be stimulated through Activin A binding with its ActRII receptor, linking both cell cytoskeleton remodeling and cell migration to quorum sensing peptide presence [28,43]. The upregulation of HIST1H4 can be associated with increased Notch1 stimulation, again connected to cancer metastasis, together with angiogenesis and NF-B production [30,44]; NF-B in turn contributes to the progression of colorectal cancer by regulating cell proliferation, angiogenesis and tumor metastasis [45]. Micro-RNA's block mRNA translation and thus impede the synthesis of specific proteins by recruiting the micro-RNA-induced silencing complex (miRISC) to target mRNAs [46]; downregulation of micro-RNA 222 and 644a thus increases KIT and -actin protein expression, respectively, thereby promoting endothelial cell proliferation and migration (angiogenesis) [36,47] and tumor cell invasiveness and motility [34].…”
Section: Discussionmentioning
confidence: 99%
“…There is a wellestablished association between tumorigenesis and inflammation as suggested in numerous studies. [29][30][31] Given this, it would be of great interest to ascertain if the association with inflammation demonstrated here with EMAST does also lead to tumorigenesis, either primarily through downregulation of specific mismatch repair genes as shown previously in our lab 9 or secondarily via frameshift mutations of specific genes containing such tetranucleotide repeats in their sequences. It is our hope that this preliminary study demonstrating the high prevalence of EMAST would foster increased research that might help clarify the biological significance of EMAST.…”
Section: Discussionmentioning
confidence: 99%